Effect of Intravenous Zoledronic Acid on Tibiofemoral Cartilage Volume Among Patients With Knee Osteoarthritis With Bone Marrow Lesions: A Randomized Clinical Trial - Cai, Guoqi (JAMA, 2020)
IMPORTANCE: A proof-of-principle study suggested that intravenous zoledronic acid may reduce knee pain and the size of bone marrow lesions in people with knee osteoarthritis, but data from large trials are lacking. OBJECTIVE: To determine the effects of intravenous zoledronic acid on knee cartilage volume loss in patients with symptomatic knee osteoarthritis and bone marrow lesions. DESIGN, SETTING, AND PARTICIPANTS: A 24-month multicenter, double-blind placebo-controlled randomized clinical trial conducted at 4 sites in Australia (1 research center and 3 hospitals). Adults aged 50 years or older with symptomatic knee osteoarthritis and subchondral bone marrow lesions detected by magnetic resonance imaging (MRI) were enrolled from November 2013 through September 2015. The final date of follow-up was October 9, 2017. INTERVENTIONS: Intravenous infusion with either 5 mg of zoledronic acid in a 100-mL saline solution (n = 113) or a placebo saline solution (n = 110) at baseline and 12 months. MAIN OUTCOMES AND MEASURES: The primary outcome was absolute change in tibiofemoral cartilage volume assessed using MRI over 24 months (the minimum clinically important difference [MCID] has not been established). Three prespecified secondary outcomes were change in knee pain assessed by a visual analog scale (0 [no pain] to 100 [unbearable pain]; MCID, 15) and the Western Ontario and McMaster Universities Osteoarthritis Index (0 [no pain] to 500 [unbearable pain]; MCID, 75) over 3, 6, 12, 18, and 24 months and change in bone marrow lesion size over 6 and 24 months (the MCID has not been established). RESULTS: Of 223 participants enrolled (mean age, 62.0 years [SD, 8.0 years]; 52% were female), 190 (85%) completed the trial. Change in tibiofemoral cartilage volume was not significantly different between the zoledronic acid group and the placebo group over 24 months (−878 mm(3) vs −919 mm(3); between-group difference, 41 mm(3) [95% CI, −79 to 161 mm(3)]; P = .50). No significant between-group differences were found for any of the prespecified secondary outcomes, including changes in knee pain assessed by a visual analog scale (−11.5 in the zoledronic acid group vs −16.8 in the placebo group; between-group difference, 5.2 [95% CI, −2.3 to 12.8]; P = .17), changes in knee pain assessed by the Western Ontario and McMaster Universities Osteoarthritis Index (−37.5 vs −58.0, respectively; between-group difference, 20.5 [95% CI, −11.2 to 52.2]; P = .21), and changes in bone marrow lesion size (−33 mm(2) vs −6 mm(2); between-group difference, −27 mm(2) [95% CI, −127 to 73 mm(2)]; P = .60) over 24 months. Adverse events were more common with zoledronic acid than with placebo (96% vs 83%, respectively) and consisted mainly of acute reactions (defined as symptoms within 3 days of administration of infusion; 87% vs 56%). CONCLUSIONS AND RELEVANCE: Among patients with symptomatic knee osteoarthritis and bone marrow lesions, yearly zoledronic acid infusions, compared with placebo, did not significantly reduce cartilage volume loss over 24 months. These findings do not support the use of zoledronic acid in the treatment of knee osteoarthritis. TRIAL REGISTRATION: anzctr.org.au Identifier: ACTRN12613000039785